ANALISIS PENGARUH KREDIBILITAS CELEBRITY ENDORSER DAN DAYA TARIK IKLAN TERHADAP BRAND AWARENESS DAN DAMPAKNYA TERHADAP BRAND ATTITUDE SABUN MANDI PADAT LIFEBUOY DI SEMARANG - Mugiono, Kharis; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2012)
Lifebuoy has always been a market leader in the toiletries industry in the category of solid soap. Nonetheless, brand value (performance brand) Lifebuoy decline, even elements of brand value (performance brand) as brand share, brand TOM and TOM ad also decreased. It can be assumed the declining strength of the brand in the minds of consumers (brand awareness) and of course will affect consumer attitudes toward the brand (brand attitude) Lifebuoy whether consumers will come back or not. In building a brand (brand awareness), the first step that must be done is the brand should be introduced first to the consumers, so that consumers can be aware of the brand, well-known brand, and ultimately a strong brand can attach minds of consumers (Ridwansyah, 2002) . One way to do that is through advertising with celebrity endorser credibility and appeal of advertising. The purpose of this study to analyze the influence of credibility of celebrity endorser and attractiveness advertising of brand awareness and its effect to brand attitude of Lifebuoy bar soap in Semarang. Sample in this study is 120 respondens who know Lifebuoy advertising. Method used is Purposive Sampling with distributes questionnaire to respondens. This study use quantitive analysis is validity and reliability test, the classical assumption test, multiple linear regression analysis, dan goodness of fit test. Based on the result of regression analysis indicate that credibility of celebrity endorser (X1) and attractiveness advertising (X2) have a positive influence and significant to brand awareness (Y1) of Lifebuoy bar soap with a regression coefficient value of 0,554 and 0,304. While the brand awareness (Y1) have a positive influence and significant to brand attitude (Y2) of Lifebuoy bar soap with a regression coefficient value of 0,791.